The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.2139/ssrn.1885052
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ethanol in Brazilian Economy: Three Decades of Progress

Abstract: Sustainable energy strategies require decision-makers in government, industry, academia and civil society alike to make choices among tradeoffs. Within the transport sector alone, ethanol has been shown to be the dominant solution among viable, low carbon options to date, yet questions remain over the economic and ecological impacts of this industry.In Brazil -the largest producer of sugarcane-based ethanol and a country with over three decades of ethanol development -we find a strong basis for evaluating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…blending bioethanol in 1931 and mandated a blend of 18 to 25% bioethanol with petrol in 2011 6 . In India, where most agricultural areas are located in the semi-arid tropics (SAT) region 33 , the government has approved the National Policy on Biofuels, which proposes blending biodiesel and bioethanol (20%) with diesel and petrol by 2017.…”
mentioning
confidence: 99%
“…blending bioethanol in 1931 and mandated a blend of 18 to 25% bioethanol with petrol in 2011 6 . In India, where most agricultural areas are located in the semi-arid tropics (SAT) region 33 , the government has approved the National Policy on Biofuels, which proposes blending biodiesel and bioethanol (20%) with diesel and petrol by 2017.…”
mentioning
confidence: 99%
“…We focus here on industrial policy targeted at non-sugar markets specifically, though others have identified 'subsidies' that support the sugarcane industry as a whole. 4 The role of the Brazilian state in the politics of sugarcane 'flexing' is usually dated to the 1975 Pró-Álcool programme, but in fact the first ethanol blend mandate of five per cent was put in place in 1931 (Costa et al 2011). That said, it was not until the 1973-74 oil price crisis that Brazil's ethanol industry really started to develop.…”
Section: Flexing and The New Geographies Of Sugarcanementioning
confidence: 99%